Heparin in the Treatment of Pulmonary Thromboembolism - Kanis, John A. (Thrombosis and Haemostasis, 1974)
A retrospective survey of patients admitted to hospital with pulmonary thromboembolism during 1971 is reported, and the methods of treatment commonly used are compared. The outcome in these patients was also compared with those receiving supportive therapy.The use of oral anticoagulants with or without the addition of heparin for the first 72 hours resulted in a significant reduction in mortality by decreasing the incidence of further fatal thromboembolism. These regimens did not significantly decrease the total number of further thromboembolic complications. Treatment with prolonged infusion of heparin without oral anticoagulants resulted in a significant reduction of both thromboembolic morbidity and mortality.Despite the difficulties of valid comparisons between methods of treatment of pulmonary thromboembolism, it is concluded that the superiority of continuous heparin infusion justifies the need for a prospective assessment of the optimum length of treatment with heparin infusion.